Evaluasi Pengaruh Suhu dan Waktu Pirolisis Biochar Bambu Betung (Dendrocalamus asper) - Andi Asmunandar; Fadjar Goembira; Slamet Raharjo; Rati Yuliarningsih (Jurnal Serambi Engineering, 2023)
AbstractThe energy security crisis and environmental pollution from the excessive use of fossil fuels are contributing to the urgent search for renewable energy resources. The crisis of shortage of fossil fuels is anticipated by using alternative fuels derived from renewable biomass. In Sawahlunto Sumatera Barat province, there is one biomass potential, namely Betung Bamboo (Dendrocalamus asper) which is used as an energy generator from former mining pits. This study aims to evaluate the pyrolysis biochar from Betung Bamboo with optimum temperature and time. In the biochar process, the decomposition of organic matter produces solid materials in the form of activated charcoal, gases and vapors and aerosols. Research to determine the optimum conditions for making biochar from Betung Bamboo has a temperature variable of 400, 500, 600, 700 and 800 oC and a time variable of 30, 45 and 60 minutes. The results of carbonization were analyzed for calorific value, volatile matter content, bound carbon content, moisture content and ash content. bound carbon content The results showed that the best parameters were obtained at 600 oC and 30 minutes, calorific value 7100 cal/g, moisture content value 4.7%, ash content value 5.73%, volatile matter content. content value of 4.7% and bonded carbon value of 78.09%. All of these parameter results meet the quality standard values of SNI 01-6235-2000, which indicates that Bambu Betung biochar has the potential to be used as a renewable alternative fuel.Keywords: bamboo, energy plant, carbonization, biochar, pyrolysis